The Influence Of Price Limit And Stock Return On Investment Contingency In Ipo Corporate For The 2020 Period On Indonesia Stock Exchange - Hartanto Dewantoro; Nendi Juhandi; Yadi Nurhayadi (Universitas Muhammadiyah Prof. DR HAMKA., 2022)
The objective of this study is to investigate the influence of Price Limit and Stock Return toward Trading Volume, Stock Return Volatility upon Corporate Initial Public Offerings for the 2020 period. In this investigation, the variables reviewed include Price Limit (X1) and Stock Return (X2) on Trading Volume (Y1), Stock Return Volatility (Y2). The research instruments were obtained through a loaded sampling of the corporate population carrying out initial public offerings in 2020. Multiple linear regression analysis was utilised as a data analysis technique and this investigation was performed by operating Eviews 10 software. The findings of this study indicate that Price Limit is positively associated with Trading Volume when the pre-change sessions. In stark contrast, in post-change sessions, the Price Limit is negatively correlated to Trading Volume. Both before and after the transformation of trading time, Stock Return significantly affects Trading Volume. Similarly, Price Limit and Stock Return simultaneously and significantly influence Trading Volume. Furthermore, Stock Return Volatility is affected by the Price Limit. Stock Return has a significant effect on Stock Return Volatility. Price Limit and Stock Return significantly influence the Stock Return Volatility.